Health-related quality of life of patients after mechanical valve replacement surgery: An integrative review. (February 2015) - Thomson Mangnall, Linda J; Gallagher, Robyn D; Sibbritt, David W; Fry, Margaret M
Background: Heart valve replacement surgery is undertaken to improve cardiac function and health-related quality of life (HRQoL). Mechanical valves are typically used for younger people (aged <65 years). Implantation of these valves comes with life-long health self-management requirements which potentially impact on HRQoL. Aims: The purpose of this study was to identify the short and long-term impact on HRQoL after mechanical valve replacement surgery. Methods: Multiple electronic databases were searched for peer-reviewed studies published between 2000–2013, which focused on patients who had mechanical valve replacement, aged <65 years, and used a valid measure of HRQoL. Results: Eight papers were included, all of which used the Short-Form 36 Health Survey (SF-36). Preoperatively, HRQoL was impaired, particularly in the SF-36 health domains of role-physical, physical-functioning, vitality and role-emotional. Postoperatively, most people had positive and sustained HRQoL improvement. In the early postoperative period all data showed significant improvement in at least four of eight health domains (physical function, role-physical, vitality, social function). Two-thirds of people also had significant improvement in an additional two health domains (general and mental-health). Whilst most people sustained HRQoL over time, one-third of younger adults (age <24 years) showed impairment in three domains (physical-function, mental-health and general-health). Conclusions: Mechanical valve replacement surgery results in important and sustained improvements in HRQoL. Future research should include investigation of HRQoL outcomes after mechanical valve replacement for specific groups such as younger adults and people in developing countries, and include evaluations of the potential impact of valve-specific factors and health self-management requirements.